The effect of acceleration on color vision - Randjelovic, Danijela; Pavlović, Miroslav (Vojnosanitetski pregled, 2020)
Background/Aim. Over 80% of all information a pilot receives during the flight is visual with color perception being one of the most important visual functions for managing an aircraft. The reception of color is of high significance in aviation due to the importance of signal tracking on instrument panels as well as the importance of visual stimulus and environment signs. There is no sufficient number of papers and studies that deal with this issue, although recent studies have shown that the connection between acceleration and color perception exists. The aim of this study was to demonstrate the correlation between pilot exposure to +Gz acceleration in human centrifuge and color perception before and after acceleration exposure. Methods. Subjects of the study were 40 military pilots, aged 35–45, with 10 and 20 years of flying experience. Pilots were exposed to +Gz acceleration (inertial force acts from head to feet) in the human centrifuge for pilot training with accelerations of +2Gz, +5.5Gz up to +7Gz. The tests focused on color perception before and after the exposure to the acceleration. Results. Out of 40 pilots examined for color vision, in 35 (87.50%) had normal results in color identification before and after +Gz; 5.00% (2 subjects) had two mistakes – reading number 5 instead of number 3, which falls within the normal trichomes, and reading number 16 instead of number 26. Three subjects (7.50%) gave their answers slower than the accepted response time. After the +7Gz exposure, 34 (85%) persons had normal results in color identification, 2 (5%) subjects made three mistakes – at numbers 5, 74 and 26; one (2.50%) pilot made four mistakes on numbers 5, 7, 74 and 26; 7.50% (3 pilots) of the subjects identified colors slower. Conclusion. Color perception in pilots is unstable on high +Gz accelerations. Exposure to +5.5Gz acceleration does not lead to significant changes in color perception, while exposure to +7Gz acceleration showed a significant percentage of reversible disturbance in color perception which lasted for 10 minutes.
Keywords: pilots; aerospace medicine; space simulation; acceleration; color vision